Performance evaluation of FDM water works system for ABS part - Marwah, Omar Mohd Faizan (2006)
Fused Deposition Modeling(FDM) is one of the Rapid Prototyping(RP) Technologies to produces plastic prototypes from acrylonitrile butadiene styrene(ABS) which has control over numerous processing variables that will impact the quality of the fabricated part. The ability to select the optimal process parameters has been a major concern for part quality improvement. This work was undertaken to determine parameters which influence the part quality for FDM Waterworks Soluble Support(WSS) system .The effect of these factors on FDM performance or response were investigated and the optimum conditions of those responses were established. Design Of Experiments (DOE) was used to perform the experiments. Experimental results were analysed by using Minitab software to obtain the significant parameters and to optimize the setting. Pareto Chart, Analysis of Variance(ANOVA), Main Effect plot and Regression were employed to determine the significant parameters and to generates recommendations of process variables setting and the associated predict build outcomes for FDM process . Finally, validation tests were conducted to verify the model of each responses against the actual results.